The Acute Effects of Cognitively Demanding Physical Activity on Inhibitory and Affective Responses in Children: An Online-Based Mixed Methods Approach - Ricardo M. G. Martins; Emiliano Mazzoli; Michael J. Duncan; Cain C. T. Clark; Emma L. J. Eyre (Children, 2022)
This online study investigated the acute effects of a cognitively demanding physical activity (CDPA) vs a simple physical activity (SPA) bout on children’s inhibitory and affective responses. Using a counterbalanced within-subjects’ crossover design, thirty-nine participants aged 9–12 years old (29 boys; Mage = 11 ± 1 years) performed a CDPA and a SPA bout online (via ZOOM) for 15 min. Inhibition (Stroop test) was measured at the baseline, 1 and 30 min following the physical activity (PA) bouts, and self-report measures of affect, mental and physical exertion were taken prior, during and post-PA. Additionally, 31 children took part in semi-structured focus groups to explore the factors affecting their enjoyment. The quantitative results suggest no significant differences on inhibitory responses, affect and physical exertion (all p > 0.05). However, the CDPA induced more mental exertion than the SPA did (p < 0.05). In the focus groups, four themes were identified: physical exertion (e.g., tiredness), social (e.g., teams/groups), environment (e.g., outdoors and competition) and emotional (e.g., fun/enjoyment). Some children (n = 18) reported that the CDPA condition confused them, and to make these activities more interesting and enjoyable, they suggested performing the activities outdoors (n = 15) and including other children as part of a group/team (n = 19). The findings suggest no additional benefit of a cognitively enriched physical activity compared to an SPA bout on the inhibitory responses, affect and enjoyment. Using the instructions provided and given the low cost, the easy administration and the minimal amount of equipment and time involved, either of the approaches may be used in a diversity of contexts (i.e., online, schools or outdoors), and it is worth exploring the effects of these conditions on other aspects of executive function.